PEMBERDAYAAN PEREMPUAN WIRAUSAHA BERBASIS INOVASI DAN TEKNOLOGI DIGITAL UNTUK PENGUATAN EKONOMI LOKAL DI DESA JABUNG, KECAMATAN PANEKAN, KABUPATEN MAGETAN, JAWA TIMUR - Henni Endah Wahanani; Swasti, Ika Korika; Sholihatin, Endang; Affro, Salma; Arimawan, Kesya Sakha Nesya (Universitas Mataram, 2025)
ABSTRACT This community engagement initiative aims to empower women entrepreneurs in Jabung Village, Panekan Subdistrict, Magetan Regency, East Java, through the implementation of product innovation and the utilization of digital technology to strengthen the local economy. The primary challenges faced by the target group include limited knowledge of digital marketing, poor packaging quality, and restricted market reach. The program was executed through a series of activities comprising training sessions, technology transfer, demonstrations, and intensive mentoring, involving 15 women entrepreneurs as core partners. A participatory approach based on Participatory Rural Appraisal (PRA) was employed, enabling active involvement of participants in every stage of the program. The outcomes indicate a significant improvement in the participants' ability to manage digital business accounts on platforms such as Tokopedia, Instagram Business, Facebook Business, and TikTok Business, with an average understanding increase of 73%, as measured by pre- and post-test evaluations. Furthermore, 85% of participants successfully created and managed online business accounts, 75% consistently uploaded product content with enhanced appeal, and 80% actively utilized social media for promotional purposes. Innovation was also evident in packaging design, with 85% of participants developing brand-identified labels, thereby enhancing consumer perception and market appeal. The tangible impacts of the program include an average sales increase of 25%, expansion of market reach beyond the village, and a rise in women's contribution to household income from 10–15% to 25–30%. These findings underscore that MSME digitalization through training, technology transfer, and branding enhancement can significantly improve women's economic independence while sustainably strengthening the local economy. Keywords: women empowerment, entrepreneurship, digitalization, product innovation, branding, local economy.